The sustainability of empire in a global perspective: the role of international trade patterns - Bonfatti, Roberto (Elsevier, 2017)
I construct a model in which a colony trades raw materials for manufactures with the mother country and the rest of the world, and can rebel at the cost of some trade disruption with the mother country. Decolonisation is more likely when the rest of the world is more abundant in manufactures, or scarcer in raw materials: this is because trade policy in the rest of the world is more favourable to a rebel colony, while trade policy within the empire is more restrictive. I use my results to explain the timing of the American Revolution, and the Latin American Revolutionary Wars. I discuss some important implications for the history of colonialism.